Comics and Archaeology - Kamash, Zena.; Soar, Katy.; Van Broeck, Leen. (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2022)
This book adds to the scant academic literature investigating how comics transmit knowledge of the past and how this refraction of the past shapes our understanding of society and politics in sometimes damaging ways. The volume comes at these questions from a specifically archaeological perspective, foregrounding the representation and narrative use of material cultures. It fulfils its objectives through three reception studies in the first part of the volume and three chapters by comic creators in the second part. All six chapters aim to grapple with a set of central questions about the power inherent in drawn images of various kinds. Dr Zena Kamash FSA is a British Iraqi archaeologist and Senior Lecturer in Roman Archaeology and Art in the Department of Classics, Royal Holloway University of London, UK. She is an expert on the heritage and archaeology of the Middle East and Britain. Her current research focuses on crafting, heritage and healing in post-conflict Syria and Iraq. Dr Katy Soar is a Senior Lecturer in Classical Archaeology at the University of Winchester, UK. Her main areas of research are Greek Archaeology, particularly the Bronze Age Aegean, and the history and reception of archaeology. Her current research focuses on depictions of Knossos on historical postcards and on the representation of antiquity in folk horror. Dr Leen Van Broeck is Honorary Research Associate in the Department of Classics at Royal Holloway University of London, UK, after completing a PhD on Tacitus there in 2018. She has taught undergraduate classicists and ancient historians on methods and approaches to (ancient) history and co-convened the Oxford Comics Network seminar series at the University of Oxford from 2019 to 2021.
Introduction: Why Comics and Archaeology? -- 'The Aliens from 2,000 B.C.!': Truth, Fiction and Pseudoarchaeology in American Comic Books -- Panels from the South Seas: Pacific Colonialism, Archaeology, and Pseudoscience in Francophone Bande Dessinée -- Making Sargon Great Again: Reuse and Reappropriation of Ancient Mesopotamian Imagery in Fan-Art of the Online Right -- Creating Comics for Public Engagement in Roman Aeclanum: Illustrating Ancient History -- "Mix, Mould, Fire!": Comic Art and Educational Outreach Inspired by Archaeology -- "They Do Things Differently There": Articulating the Unfamiliar Past in Community Heritage Comics.
Keywords: Comic books, strips, etc.-Influence on mass media; Archaeology; History, Ancient; Comics Studies; Archaeology; Classical Studies